An unusual complication of septic sacroiliitis: Hepatic and splenic infarction after iliac vein thrombosis - Danışan, Gürkan; Taş, Nurmuhammet; Polat, Gökhan; Oğul, Hayri (Journal of Surgery and Medicine, 2019)
Septic sacroiliitis typically presents with non-specific symptoms such as limping gait, radiating pain in the hip and lumbar region and fever. Differential diagnoses include pelvic abscess, lumbar disc herniation or septic arthritis of the hip, and misdiagnosis is common. Magnetic resonance imagining (MRI) greatly enhanced the ability to determine the extent of infection arising from the sacroiliac joint. We hereby present a rare case of hepatic and splenic infarction secondary to septic thrombophlebitis in a patient with sacroiliitis.